Enteropathogenic Bacteria from Padang Food in Jatinangor September–October 2012 - Syed Anwar Husain; Sunarjati Sudigdoadi; Abdullah Firmansyah W. (Faculty of Medicine Universitas Padjadjaran, 2015)
Background: Diarrhea is a food borne disease and still a major health problem in Indonesia. Padang foodis a popular cuisine and is exposed on an opened display, sometimes for many hours in room temperature,catering favorable conditions for bacterial growth. This study is undertaken to identify enteropathogenicbacteria on food in Padang restaurants located in Jatinangor, SumedangMethods: A laboratory study was conducted in the microbiology laboratory of the Department ofMicrobiology in the Faculty of Medicine, Universitas Padjadjaran, during September–October 2012. Sampleswere collected from 5 Padang restaurants located in Jatinangor using systematic random sampling. Fromeach restaurant, 4 wet samples were collected approximately 2–4 hours after being left open on the display shelves from sambal hijau, sambal merah, gulai babat and gulai nangka, cultured in tryptic soy broth (TSB) and incubated for 24 hours at 37 ºC, then inoculated in Mac Conkey agar and incubated for 24 hours at 37 ºC. Gram-staining was performed to identify gram-negative rods. The bacteria were put through biochemical tests.Results: Four species bacteria from the Enterobacteriaceae family were identified. The most frequent bacteria which was identified in the samples was Shigella sp (4 from 20), followed by Klebsiella pneumonia(3 from 20), Escherichia coli and Pseudomonas sp were less identified.Conclusions: Various Padang foods have potential risks of bacterial contamination due to the preparation,handling, and serving. It should be considered that the prepared food should be covered and placed in foodwarmers, ensuring warm food for hours. [AMJ.2015;2(1):241–44]